The Counter-Issues of Tanah Datar Government Regarding the Coverage News of Terrorism - Okditazeini, Vannyora (School of Journalism, Faculty of Communication Sciences, Universitas Padjadjaran, 2024)
Tanah Datar, known for its rich Minangkabau cultural heritage and dedication to the philosophy of Kitabullah, is facing a disturbing trend. Despite its deep-rooted religious values, Densus88 has reported that the city has the second-highest number of NII terrorist personnel in West Sumatra. This revelation exposes a stark contrast between Tanah Datar's cultural identity and terrorism reports. The government must act to prevent further misconceptions. This research aimed to evaluate the distribution and focus of content related to terrorism on internal and external media sources and the government's approach to countering these issues. The study employed content analysis to examine the news by the Tanah Datar Regency government. This study applied a content analysis approach by Kripendorff, which involved three stages: crawling, coding, and abstracting. In the first phase of analysis, the study found 50 units of data from internal sources and 229 from external sources. The research findings indicated that news related to terrorism in Tanah Datar is only found in external media sources. The top three counter-issues pursued by the government include government branding with 158 posts (69%), and tourism impressions with 16 posts (7%). and health literacy with 11 posts (4.8%). The government has adopted an unconventional approach to address terrorism issues. Rather than reporting such issues on official channels, they opt to utilize media partners, offering an alternative strategy to tackle terrorism.